2008
DOI: 10.1124/mol.108.049486
|View full text |Cite
|
Sign up to set email alerts
|

Thermostable Variants of Cocaine Esterase for Long-Time Protection against Cocaine Toxicity

Abstract: Enhancing cocaine metabolism by administration of cocaine esterase (CocE) has been recognized as a promising treatment strategy for cocaine overdose and addiction, because CocE is the most efficient native enzyme for metabolizing the naturally occurring cocaine yet identified. A major obstacle to the clinical application of CocE is the thermoinstability of native CocE with a half-life of only a few minutes at physiological temperature (37°C). Here we report thermostable variants of CocE developed through ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
155
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 82 publications
(165 citation statements)
references
References 37 publications
9
155
0
1
Order By: Relevance
“…In an extension of previous findings with DM CocE (T172R/G173Q CocE or RQ CocE; Collins et al, 2009Collins et al, , 2011aGao et al, 2009;Narasimhan et al, 2010), the current studies evaluated impact of introducing two cysteine residues at the dimer interface, in combination with the PEGylation of this crosslinked CocE dimer (PEG-CCRQ CocE; Narasimhan et al, 2011) on duration and effectiveness of CocE to alter the behavioral effects of cocaine. Importantly, just as these changes did not alter the enzymatic activity of PEG-CCRQ CocE in vitro , the DM (RQ) and PEG-CCRQ forms of CocE appeared to be equally effective at eliminating cocaine in vivo as both enzymes produced at least 10-fold rightward shifts in the reinforcing effects of cocaine when comparable doses of B3 mg/kg were administered immediately before the start of cocaine self-administration sessions (Collins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In an extension of previous findings with DM CocE (T172R/G173Q CocE or RQ CocE; Collins et al, 2009Collins et al, , 2011aGao et al, 2009;Narasimhan et al, 2010), the current studies evaluated impact of introducing two cysteine residues at the dimer interface, in combination with the PEGylation of this crosslinked CocE dimer (PEG-CCRQ CocE; Narasimhan et al, 2011) on duration and effectiveness of CocE to alter the behavioral effects of cocaine. Importantly, just as these changes did not alter the enzymatic activity of PEG-CCRQ CocE in vitro , the DM (RQ) and PEG-CCRQ forms of CocE appeared to be equally effective at eliminating cocaine in vivo as both enzymes produced at least 10-fold rightward shifts in the reinforcing effects of cocaine when comparable doses of B3 mg/kg were administered immediately before the start of cocaine self-administration sessions (Collins et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although the wild-type (wt) form of CocE is capable of dose dependently protecting mice and rats against the cardiovascular, convulsant, and lethal effects of cocaine, it is rapidly inactivated at body temperature resulting in an in vivo half-life of B15 min (Cooper et al, 2006;Jutkiewicz et al, 2009;Ko et al, 2007Ko et al, , 2009Wood et al, 2010). Sitedirected mutagenesis studies aimed at improving the thermostability of CocE have identified an equally efficient mutant CocE (T172R/G173Q CocE, RQ CocE, DM CocE) with an in vivo half-life of B4.5 h in mice (Gao et al, 2009;Narasimhan et al, 2010), and a high degree of pharmacologic specificity (Brim et al, 2011). In addition to dose dependently inhibiting the cardiovascular, convulsant, lethal, and reinforcing effects of cocaine in rats (Collins et al, 2009(Collins et al, , 2011b, DM CocE has also been shown to effectively reverse the cardiovascular effects associated with large intravenous (IV) doses of cocaine in rhesus monkeys (Collins et al, 2011a).…”
Section: Introductionmentioning
confidence: 99%
“…Isolated from the MB1 strain of Rhodococcus sp. found in the Rhizosphere soil surrounding the coca plant, CocE has a high V max toward cocaine (V max ϭ 2300 min Ϫ1 ) (Gao et al, 2009) and produces the same products as BchE (Bresler et al, 2000). CocE has previously been shown to block cocaine-induced cardiac disturbance, neurological changes, and lethality in rodents when administered before or after cocaine (Cooper et al, 2006;Jutkiewicz et al, 2009;Ko et al, 2007;Wood et al, 2010).…”
mentioning
confidence: 99%
“…The wild-type (wt) CocE cannot be used as a pharmacotherapy for cocaine abuse because of its 13.7-min half-life at 37°C (Cooper et al, 2006;Ko et al, 2007;Gao et al, 2009). We have previously identified a mutant of CocE (T172R and G173Q) that extends the half-life of CocE to ϳ4.5 h, as assessed by in vitro kinetic assays (at 37°C) or in vivo by protection against cocaine-induced lethality in mice (Gao et al, 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation